Analysis of Application of the TOD Concept in the Istora Senayan Area - Muhamad Taki, Herika; Wibowo, Salsabila Dhania; Bethaziarennur, Muhammad Zaydan; Erlangga, Kelvin (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2026)
TOD (Transit Oriented Development) is a concept of developing a mixed area that is integrated with transportation modes. This article aims to analyze the application of the TOD concept in the Istora-Senayan area. Research of The Application of the TOD concept in Istora Senayan area generally combines primary and secondary data. Primary data consists of field observation: recording real conditions of pedestrian paths, cycling infrastructure, transit access, land use, and connectivity. Spatial mapping/GIS analysis: mapping walking distance radius (400-800 m from station), measuring accessibility, block permeability, and connectivity (74,4% of the area within 800m walking distance to transit). Surveys: researchers interpret TOD Indicators (Walking, Cycling, transit, connectivity) into measurable variables and applying scoring methods. Interviews: using design and planning studies to understand stakeholder perspectives and land use problems.  Secondary data: Policy and regulatory documents: TOD Standard (ITDP), DKI Jakarta TOD regulations (Pergub 67/2019), and MRT Jakarta Planning Guidelines. Planning maps and land use data: Land allocation data (residential, commercial, office, etc.) to analyze development patterns and ridership potential. Literature review: Journals, Theses, and urban design documents to define TOD Variable and theoretical frameworks. Data analysis in TOD studies is generally descriptive-quantitative + spatial evaluation, supported by TOD indicator frameworks (e.g., ITDP TOD Standard and Jakarta TOD regulation). Spatial Analysis Interpretation. Spatial analysis explains the relationship between space and TOD performance. A. Walkability Coverage Analysis. 1. Buffer (400–800 m) used to measure walkable catchment. 2. Interpretation: high coverage indicates strong TOD accessibility. Land-Use Mix Analysis. When reviewed based on the concept of TOD, the MRT Istora-Senayan station is included in the TOD development area, because it meets 2 criteria, namely mixed use and proximity to transit points. Based on the results, it can be concluded that the Istora and Senayan MRT Stations have fulfilled and implemented the TOD development concept. This is evidenced by the presence of mixed land use and the integration between the MRT and BRT systems.